Usaha Majlis Perbandaran Alor Gajah dalam menggalakkan perniagaan sektor tidak formal di Bandar Baru Masjid Tanah, Alor Gajah Melaka - Abdullah, Rohaya (2007)
The Non Formal Business Sector plays an important role in the development of certain area especially in the city, however the government has to take a serious attention in developing this Non Formal Sector’s in order to curb the environmental cleanliness problem and health of the public. The existing of this non formal sector may assist the government to generate the economic of the city resources besides will benefit the development of the local economic. However, the development of the Non Formal Business Sector which is not plan and beyond control may contribute to the problem of environmental cleanliness phenomenon to the city, traffic congestion and threatened the trader’s security and abraded the quality of city area’s view. Therefore, as a local authority, Alor Gajah Municipal Council (MPAG) shall not ignore the situation in the city area. MPAG shall plan, arrange, control and develop the Non Formal Business Sector to determine the cleanliness, security and comfort in the city area. Hence, this research will identify the role and importance of the Non Formal Business Sector to the public and the problems face by the traders and also the visitors. The traders and the visitor’s perception towards the physical facilities necessities for this non formal sector is determine through the questionnaires form which are circulated at five chosen locations in Bandar Baru Masjid Tanah, then it will be analysed using the quantitative method that is frequency method, likert scala method and cross schedule method. The result of the research shows that face by the traders and the public among others is the size of the business is too narrow and insufficient of physical facilities in the existing business stalls. A few suggestion are proposed to MPAG in order to assist improving the Non Formal Business Sector activities and to actualize its own business identity environment, that is clean and suitable besides fulfilled the planning requirement and the needs of the local society. However, it is difficult to carry out the development planning for the public utilities and in most of the local authorities without the involvement from the agency such as the Developer, Mara and UDA. Finally, the conclusion is based on the result of the analysis to equilibrate the existing development.